2019
DOI: 10.1007/s00018-019-03041-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional high-throughput screening reveals miR-323a-5p and miR-342-5p as new tumor-suppressive microRNA for neuroblastoma

Abstract: Current therapies for most non-infectious diseases are directed at or affect functionality of the human translated genome, barely 2% of all genetic information. By contrast, the therapeutic potential of targeting the transcriptome, ~ 70% of the genome, remains largely unexplored. RNA therapeutics is an emerging field that widens the range of druggable targets and includes elements such as microRNA. Here, we sought to screen for microRNA with tumor-suppressive functions in neuroblastoma, an aggressive pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 31 publications
1
24
1
Order By: Relevance
“…Of note, decreased levels of miR‐342‐5p were also found in neonatal patients with moderate/severe BPD, highlighting its role in the human disease setting. As miR‐342‐5p has largely been associated with tumour suppression (Lindholm et al, 2019; Soriano et al, 2019) and is likely non‐oncogenic, miR‐342‐5p mimic therapy may show promise in treating or preventing BPD. Such a mimic therapy should be targeted at T2AECs in order to enhance the therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, decreased levels of miR‐342‐5p were also found in neonatal patients with moderate/severe BPD, highlighting its role in the human disease setting. As miR‐342‐5p has largely been associated with tumour suppression (Lindholm et al, 2019; Soriano et al, 2019) and is likely non‐oncogenic, miR‐342‐5p mimic therapy may show promise in treating or preventing BPD. Such a mimic therapy should be targeted at T2AECs in order to enhance the therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput functional screenings (HTFSs) have used miRNA-ASOs or RNA molecules designed to mimic endogenous mature miRNA (miRNA-mimics), to identify species with an effect in the expression of dosage-sensitive genes, in reporter assays 13, 14. In addition, most HTFS analyses have evaluated the effect of a moderate number of miRNA-mimics or -ASOs in tumorigenic outcomes, including cell invasiveness, 15 tumor cell death, 16 or cell growth 17, 18. HTFS studies to generally identify sncRNAs with a role in differentiated neuronal cell viability are missing.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that CDCA5, which is transcribed by E2F1, promotes oncogenesis by enhancing cell proliferation and inhibiting apoptosis via the AKT pathway in HCC [30]. In addition, INCENP dysregulation has also been confirmed to be related to the occurrence and development of a variety of tumors [31][32][33][34]. INCENP depletion can suppress neuroblastoma cell growth by inducing polyploidization, apoptosis, and senescence [31].…”
Section: Discussionmentioning
confidence: 99%